Obtenção e caracterização de heteroestruturas epitaxiais magnetoelétricas de [KNbO3]0,9-[BaNi1/2Nb1/2O3-]0,1 e [La0,7Sr0,3MnO3] - Naranjo López, Andrea (2016)
Magnetoelectric materials have been extensively studied in the last decade, particularly due to the applicability for sensors, attenuators, transformers and others. Hence as an objective for this work we propose a study on the fabrication and characterization of materials that may be used as extrinsic magnetoelectrics. Our proposal consists in producing by pulsed laser deposition bilayers of ferroelectric thin films [KNbO_3]_(0,9)-[BaNi_(1/2)Nb_(1/2)O_(3−)]_(0,1) (KBNNO), grown on magnetic thin films [La_(0,7)Sr_(0,3)MnO_3] (LSMO). Focusing our interest on the KBNNO, because it is a relatively new material, and there is not enough information about its possible applications as magnetoelectric, just as there are for photovoltaic application. Initially, we made a detailed study on the dependence of the ceramic target densification of the ferroelectric phase KBNNO with the sintering temperature, with the aim to determine the appropriate parameters in the fabrication of the ceramic target, obtained by solid state reaction method. It was possible to achive ceramics targets with relative densities greater than 94 %. The structural and morphological properties of the ceramic targets and thin films were studied by X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques, respectively. The X-ray diffraction profile confirmed the phases and crystal structures of the samples. Particularly, the thin films showed an oriented growth (epitaxial) with formation of nanopilares with different diameters and heights depending on the deposition parameters. The electrical properties were determinated by ferroelectric hysteresis and electric impedance spectroscopy. The magnetoelectric and optical properties were determined by magnetoelectric coupling and photoluminescence measurments, respectively. For the ceramic samples the ferroelectric and dielectric behaviors were confirmed, and for the thin films a magnetoelectric coupling between the ferroelectric and magnetostrictive phases was found. Finally, the value of the gap for ceramic KBNNO was found to be aroud 1.248eV, this result is consistent with values reported in the literature for this material.